Can balance exercise programmes improve balance and related physical performance measures in people with dementia? A systematic review - Suttanon, P.; Hill, Keith; Said, C.; Dodd, K. (2010)
This review presents the physical performance outcomes of randomised trials investigating exercise programmes that included balance exercise for older people with dementia. A systematic literature search through five computerised bibliographic databases until February 2009 was carried out. Of 1,038 potentially relevant published articles, only seven met the inclusion criteria and were extracted. Findings from the review for a total of 632 participants showed that almost all of the included studies addressed exercise or physical activities as the main intervention; however, only two of the studies focused on balance exercise. The effect size values varied from no effect (0. 00) to a large effect (3. 29) of the interventions for a range of physical performance outcome measures. Findings also suggest that it is feasible to conduct exercise programmes with older people with dementia. However, further studies with more specific exercise designed to improve balance performance in order to prevent falls are required for older people with dementia. © 2010 European Group for Research into Elderly and Physical Activity (EGREPA).